Group investigation and rotation trio exchange learning model: The impact on students' mathematical problem-solving abilities - Dina, Nurul Rahma; Siregar, Tanti Jumaisyaroh (Universitas Islam Negeri Raden Intan Lampung, 2022)
Mathematics is a basic science that has an important role. So, to achieve the objectives of learning mathematics, mathematical problem-solving abilities are needed. The mathematical problem-solving ability of the students of SMP PAB 3 Saintis at Deli Serdang is still very low. It is suspected that the Group Investigation and Rotation Trio Exchange learning models can improve students' mathematical problem-solving abilities. The purpose of this research was to determine the effect of students' problem-solving abilities taught using Group Investigation and Rotation Trio Exchange. Data collection techniques in this research use tests. The tests carried out were students' mathematical problem-solving abilities (pretest and post-test). The data that has been collected is then analyzed using the validity test, reliability test, normality test, homogeneity test, and t-test. Based on the results of the analysis, it was found that the problem-solving abilities of students taught using Group Investigation were more effective because students using the Group Investigation model had higher learning outcomes with an average score of 83.83 compared to those using Rotation Trio Exchange which obtained an average score of 75.32. Therefore, students' mathematical problem-solving abilities are more appropriate to be taught using Group Investigation rather than Rotation Trio Exchange.